Evolution and diversity of community-associated methicillin-resistant Staphylococcus aureus in a geographical region - Coombs, Geoffrey; Monecke, S.; Pearson, J.; Tan, H.; Kong, Y.; Wilson, L.; Ehricht, R.; O'Brien, Frances; Christiansen, Keryn (BioMed Central, 2011)
Background: Community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) was first reported in remote regions of Western Australia and is now the predominant MRSA isolated in the state. The objective of this study is to determine the genetic relatedness of Western Australian CA-MRSA clones within different multilocus sequence type (MLST) clonal clusters providing an insight into the frequency of S. aureus SCCmec acquisition within a region. Results: The CA-MRSA population in Western Australia is genetically diverse consisting of 83 unique pulsed-field gel electrophoresis strains from which 46 MLSTs have been characterised. Forty five of these sequence types are from 18 MLST clonal clusters and two singletons. While SCCmec IV and V are the predominant SCCmec elements, SCCmec VIII and several novel and composite SCCmec elements are present. The emergence of MRSA in diverse S. aureus clonal clusters suggests horizontal transmission of the SCCmec element has occurred on multiple occasions. Furthermore DNA microarray and spa typing suggests horizontal transfer of SCCmec elements has also occurred within the same CC. For many single and double locus variant CA-MRSA clones only a few isolates have been detected.Conclusions: Although multiple CA-MRSA clones have evolved in the Western Australian community only three clones have successfully adapted to the Western Australian community environment. These data suggest the successful evolution of a CA-MRSA clone may not only depend on the mobility of the SCCmec element but also on other genetic determinants.